A vindication of the conduct of Captain Christopher Middleton, in a late voyage on board His Majesty's ship the Furnace, for discovering a north-west passage to the Western American ocean . [electronic resource] : in answer to certain objections and aspersions of Arthur Dobbs, Esq. - Middleton, Christopher, d. 1770.; Dobbs, Arthur, 1689-1765. (London : Printed by the author's appointment, and sold by Jacob Robinson ., 1743)
Includes publisher's list. After p. 168 comes 177; the hiatus is not supplied. Electronic reproduction. Mode of access: Internet. 44